Effect of altitude, slope and geographic exposure on tree fern distribution - Antúnez, Pablo; López-Serrano, Pablito Marcelo; González-Adame, Gabriel; Rubio Camacho, Ernesto Alonso; Mendoza-Díaz, María Magdalena (Instituto de Ecología, A.C., 2022)
Background and Aims: Knowledge of the topographic characteristics of a site is important to understand the local diversity and for proper monitoring of the response of plants with high conservation interest to climate change or land use change. The objective was to examine the distribution pattern of four tree fern species in function of elevation above sea level, exposure, and slope along an altitudinal continuum.Methods: The effect of altitude, slope and geographic exposure on the distribution of Alsophila firma, Cyathea bicrenata, Cyathea myosuroides and Sphaeropteris horrida was studied in La Chinantla, northern Oaxaca, Mexico. The hypothesis of homogeneity of proportions to the change of topographic factors was verified by the Chi square test and the degree of incidence with polynomial functions.Key results: Significant differences between the proportions of each species as a function of each topographic variable were observed. On average, the slope showed an index of significance 43.48 times greater than geographic orientation and 2.50 times greater than elevation above sea level. We observed similarities between the partial niche of Cyathea bicrenata and Alsophila firma, but dissimilarities between Alsophila firma and Cyathea myosuroides.Conclusions: The distribution of tree fern proportions at the local level is discontinuous and non-uniform, attributable to the action of the predominant local factors, mainly topography. Heterogeneous topography leads to highly random distribution patterns of the species studied.